Evaluation of coconut water neutralized by different agents on the viability of human fibroblasts: an in vitro study - Priscilla Barbosa Ferreira SOARES; Aletheia Moraes ROCHA; Manuella Verdinelli de Paula REIS; Camilla Christian Gomes MOURA; Carlos José SOARES
Abstract Objective This study evaluated four types of pH adjustment of the coconut water (CW) on viability of human fibroblasts (HFF). Material and method Natural and industrialized CW were adjusted to pH 7.0 using: (1) Sodium Hidroxide (NaOH), (2) Sodium bicarbonate (NaHCO3), (3) Triethanolamine (C6H15NO3), (4) 2-Amino-2-Methil-1-Propanol (C4H11NO). Fibroblasts were plated at 2×104/ well in 96 well plates and maintained in the CW solutions for 2 h and 4 h. Positive control was represented by HFF maintained in DMEM and the negative control by tap water. Cell viability was analyzed by MTT formazan method. Data were analyzed by 3-way ANOVA followed by Tukey's and Dunnet's test. Result There are no significant effect on the cell viability regarding type of CW, period of evaluation, and the interactions between CW and period of evaluation, CW and pH adjustment method, pH adjustment method and period of evaluation (p>0.05). Conclusion The product used for CW pH adjustment did not influenced HFF viability, thought there are a tendency of better performance in natural CW.